Returnable plastic crate rental services and market linkages for fruit and vegetable farmers in Nigeria - Yami, Mesay; Liverpool-Tasie, Saweda Lenis Onipede; Tesfamicheal, W.; Oyakhilomen, O.; Yamauchi, Futoshi; Bubayaro, M.; Feleke, S.; Abdoulaye, Tahirou (CGIAR System Organization, 2024)
Plastic crates drastically reduce food loss while stored and/ or transported. The crates should replace the traditional raffia baskets that lead to high post-harvest losses during storage and transportation. The adoption rate is currently low because the price is high, and/or the benefits of using plastic crates must be better understood. The majority of plastic crates are on a rental basis.